2021
DOI: 10.3389/fcell.2021.654084
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor-Induced Tendon Stem Cell Conditioned Medium Promotes Healing of Injured Achilles Tendon

Abstract: Tendon repair is a medical challenge. Our present study investigated the effectiveness of acellular therapy consisting of conditioned medium (CM) of tendon stem cells (TSCs) induced with hepatocyte growth factor (HGF) in promoting the healing of injured Achilles tendon in a rat model. Proteomic analysis of soluble substances in the CM was performed using an array chip, and bioinformatic analysis was carried out to evaluate interactions among the factors. The effects of CM on viability and migratory capacity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Although most of the studies describing the incorporation of bioactive molecules were performed on randomly oriented fibers [ 85 , 153 , 155 , 157 , 161 , 165 , 171 , 172 ], which do not mimic tendon structure, their description can be of great interest since they could represent novel immunoinformed strategies to develop functionalized tendon biomimetic scaffolds aimed at boosting scaffold’s efficacy and its regenerative potential [ 85 , 153 , 155 , 157 , 161 , 165 , 171 , 172 ]. Within these investigations, a wide range of biomolecules used can be found.…”
Section: Scaffold Immunoengineering Strategies For Tendon Te Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most of the studies describing the incorporation of bioactive molecules were performed on randomly oriented fibers [ 85 , 153 , 155 , 157 , 161 , 165 , 171 , 172 ], which do not mimic tendon structure, their description can be of great interest since they could represent novel immunoinformed strategies to develop functionalized tendon biomimetic scaffolds aimed at boosting scaffold’s efficacy and its regenerative potential [ 85 , 153 , 155 , 157 , 161 , 165 , 171 , 172 ]. Within these investigations, a wide range of biomolecules used can be found.…”
Section: Scaffold Immunoengineering Strategies For Tendon Te Applicationsmentioning
confidence: 99%
“…Apart from the studies regarding the effects of the bioactive molecules on improving the teno-inductive potential of electrospun scaffolds, other investigations concerning the use of different kinds of biocompounds to improve the modulatory effects of the immune system in tenocytes and stem cells were performed [ 163 , 164 , 165 , 166 ]. As previously mentioned, some pro-inflammatory molecules such as IFN-γ induce the secretion of immunomodulatory proteins, such as COX-2, PGE 2 or IDO [ 177 ] in the MSCs.…”
Section: Scaffold Immunoengineering Strategies For Tendon Te Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further illustrate the differences in scale between the detected quantities of proteins in the studied tenocyte-derived lyophilized APIs and the reported therapeutic doses of the same proteins, selected publications in the field of regenerative medicine presenting the use of individual growth factors were analyzed [50][51][52][53]. Akita et al have reported and discussed the use of FGF-2 at doses of 100 µg/mL in wound healing applications, which correspond to the approved growth factor concentration for skin ulcers in human patients [50].…”
Section: Lyophilized Progenitor Tenocyte Derivative Apis Present Extensive Physicochemical Stability and Contain Low Quantities Of Multipmentioning
confidence: 99%
“…Akita et al have reported and discussed the use of FGF-2 at doses of 100 µg/mL in wound healing applications, which correspond to the approved growth factor concentration for skin ulcers in human patients [50]. Zhang et al have reported the use of tendon stem cell (i.e., stimulated with 10-80 ng/mL HGF) conditioned medium for the healing promotion of injured Achilles tendons [51]. Hagerott et al have described the treatment of murine dermal wounds using topical FGF-1 in quantities of 0.6-6.0 µg/cm 2 [52].…”
Section: Lyophilized Progenitor Tenocyte Derivative Apis Present Extensive Physicochemical Stability and Contain Low Quantities Of Multipmentioning
confidence: 99%